Anne R. Bromberg y Karl Kilinski II. Gods, Men and Heroes. Ancient Art at the Dallas Museum of Art. Dallas: Dallas Museum of Art-University of Washington Press, 1996. 144 pp., ilus., maps. - José Carlos Castañeda Reyes (El Colegio de México, A.C., 1999)
-